Hydrodynamics of an U-shaped OWC device in a two-layer fluid system. (December 2022) - Trivedi, Kshma; Koley, Santanu
Abstract: In this article, the effectiveness of an U-shaped "oscillating water column wave energy converter device (OWC-WEC)" is investigated in a two-layer fluid system. To solve the BVP, the "dual boundary element method" (DBEM) is employed. Further, the response of shape parameters on the effectiveness of OWC-WEC is studied in "surface mode" (SM) and "internal mode" (IM), respectively. It is seen that in the surface mode, the variation in the efficiency curve as a consequence of the change in chamber's length and the lip wall's draft adopt a similar resonating pattern as in single layer fluid. Furthermore, negligible change is appeared in the efficiency curve due to the change in density ratios in SM mode. Moreover, for smaller and moderate wavenumbers, the variation in the efficiency curve due to the various chamber length, draft of the lip wall and density ratios in internal mode shows highly oscillatory behavior. In addition, this oscillatory behavior vanishes in the short-wave zone.